1990
DOI: 10.1038/bjc.1990.43
|View full text |Cite
|
Sign up to set email alerts
|

Immunoscintigraphy of human lung squamous cell carcinoma using an iodine-131 labelled monoclonal antibody (Po66)

Abstract: Summary Monoclonal antibody (McAb) Po66 has been obtained by immunisation of mice against a human lung squamous cell carcinoma. The in vitro reactivity of the antibody with cancer cells and its ability to localise in human lung cancer xenografts growing in nude mice have been reported earlier. Presented here is the first clinical evaluation of the antibody for scintigraphic detection of tumours. Thirty-three patients with histologically confirmed primary non-small cell lung carcinoma were investigated. Twenty-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1993
1993
1996
1996

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…In patients with lung cancer several studies have shown that immunoscintigraphy may detect the primary tumour and the possible presence of regional and distant metastases. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] In 13 of 17 clinical investigations so far available for evaluation, tumour targeting was attempted with anti-carcinoembryonic antigen (CEA) antibodies 2-46-101214-17 and anti-CEA immunoscintigraphy can be regarded as the standard for immunoscintigraphic diagnosis. In a recent review of studies of anti-CEA immunoscintigraphy in lung cancer'9 the average detection rates for primary, mediastinal, and distant tumour metastases were 87% (216 of 248 patients), 70% (49 of 70), and 84% (109 of 130), respectively.…”
mentioning
confidence: 99%
“…In patients with lung cancer several studies have shown that immunoscintigraphy may detect the primary tumour and the possible presence of regional and distant metastases. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] In 13 of 17 clinical investigations so far available for evaluation, tumour targeting was attempted with anti-carcinoembryonic antigen (CEA) antibodies 2-46-101214-17 and anti-CEA immunoscintigraphy can be regarded as the standard for immunoscintigraphic diagnosis. In a recent review of studies of anti-CEA immunoscintigraphy in lung cancer'9 the average detection rates for primary, mediastinal, and distant tumour metastases were 87% (216 of 248 patients), 70% (49 of 70), and 84% (109 of 130), respectively.…”
mentioning
confidence: 99%